Evaluation of Diagnostic Efficacy of Transvaginal Sonography, Hysteroscopy and Histopathological Examination in Cases of Abnormal Uterine Bleeding - Hugo Ruiz Flores, Ignacio Torres Campos, Álvaro Vargas Vega (Academic Journal of Clinicians, 2024)
Background: Hypothyroidism is a common endocrine disorder that can have significant effects on reproductive health. This study aims to assess the prevalence of hypothyroidism in infertile women and evaluate the impact of hypothyroidism treatment on infertility outcomes. Objective: To compare the diagnostic efficacy of Transvaginal Sonography (TVS), Hysteroscopy, and Histopathological Examination in identifying the underlying causes of Abnormal Uterine Bleeding Methods: A cross-sectional study was conducted involving 200 infertile women attending a fertility clinic. Participants were screened for thyroid function using serum TSH and free T4 levels. Those diagnosed with hypothyroidism were treated with levothyroxine and followed for six months. Infertility parameters, including menstrual cycle regularity, ovulation rates, and pregnancy outcomes, were recorded pre- and post-treatment. Results: The prevalence of hypothyroidism among the study population was found to be 25%. Following treatment, a significant improvement was observed in menstrual regularity (p < 0.01) and ovulation rates (p < 0.05). Additionally, the pregnancy rate among treated women increased from 10% to 35% within six months (p < 0.001). Conclusion: The high prevalence of hypothyroidism in infertile women underscores the need for routine thyroid screening in this population. Treatment of hypothyroidism significantly improves reproductive outcomes, highlighting the importance of early diagnosis and management in enhancing fertility. Further research is warranted to explore the underlying mechanisms linking thyroid function and infertility.